The voltage concentration in the vicinity of spherical mine workings of deep foundations - Arinov, E.; Ispulov, N.A. (Ye.A.Buketov Karaganda State University Publishing house, 2014)
A solution for the determination of voltage concentrations in the vicinity of spherical mine workings of deep foundations is given. A system of differential equations of equilibrium in a spherical coordinate system is used for solving the task. The case of spheroidal deformation in axisymmetric loading is considered.
Терең орналасқан сфера түріндегі тау-кен тұтқыр маңайындағы кернеулердің шоғырлануы
Концентрация напряжений в окрестности горных выработок сферической формы глубокого заложения
Keywords: mining; elastic deformation; movement vectors; differential equations; boundary value problems